The role of the intestinal microbiota in eating disorders – bulimia nervosa and binge eating disorder. (June 2021) - Herman, Anna; Bajaka, Armand
Highlights: Increasing number of studies confirm the relationship between the composition of intestinal microbiota and the regulation of appetite, mood and body mass. Intestinal dysbiosis can play an important role in the etiology of binge eating episodes. The composition of the intestinal microbiota can be modulated by antibiotics, probiotics, prebiotics and faecal microbiota transplantation. Understanding bidirectional relationship between bulimia nervosa and binge eating disorder and alterations in the intestinal microbiota suggest the utility of new treatment methods of these disorders aimed at improving the composition of the intestinal microflora. Abstract: Bulimia nervosa (BN) and binge eating disorder (BED) are both eating disorders (EDs) characterised by episodes of overeating in which large amounts of food are consumed in short periods. The aetiology of BN and BED is not fully understood. Psychological and social factors influence the development of BN and BED, but biological factors such as neurohormones that regulate hunger and satiety, or neurotransmitters responsible for mood and anxiety play a significant role in sustaining symptoms. Increasing numbers of studies confirm the relationship between the composition of intestinal microbiota and the regulation of appetite, mood, and body mass. In this manuscript, we will describe the mechanisms by which intestinal dysbiosis can play an important role in the aetiology of binge eating episodes based on current understanding. Understanding the two-way relationship between BN and BED and alterations in the intestinal microbiota suggest the utility of new treatment methods of these disorders aimed at improving the composition of the intestinal microflora.